Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Sari Roti pada Indomaret Griya Piayu di Kota Batam - Erik Nelson Sibuea; Triana Ananda Rustam (eCo-Buss, 2022)
In today's era, there are many business people with similar product commodities. Products that are able to provide the highest satisfaction will definitely get a place in the hearts of consumers and can survive in the market. The purpose of this study was to find the effect of price, promotion, and product quality on the purchasing decision of Sari Roti at Indomaret Griya Piayu in Batam City. The sample technique used is simple random sampling which uses questionnaires to 206 respondents, namely visitors who shop at Indomaret Griya Piayu. The analysis used multiple linear regression analysis with SPSS 25. The results showed that the results of the significant level of price effect were 0.001 < 0.05, the effect of promotion resulted in a significant level of 0.01 < 0.05, and the product quality level of significance was 0.000 < 0.05. which means the significant value of the three variables has a positive and significant effect on purchasing decisions. And the simultaneous effect of price, promotion, and product quality on purchasing decisions.